2019
DOI: 10.1016/j.celrep.2019.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule and CRISPR Screening Converge to Reveal Receptor Tyrosine Kinase Dependencies in Pediatric Rhabdoid Tumors

Abstract: Highlights d Rhabdoid cell lines and tumors have few mutations yet highly express a range of RTKs d RTKs and SHP2 are vulnerabilities in small-molecule and CRISPR-knockout screens d RTK inhibitors are effective against a xenografted rhabdoid mouse model in vivo d Perturbational screens may identify vulnerabilities not detectable in genomic analyses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…In recent years, CRISPR/Cas9 has been widely applied in altering genomes to activate or to repress the expression of genes; thus, its application accelerates the study of the mechanism of tumorigenesis and the development of cancer therapy ( Lee et al, 2019 ). A recent study demonstrated that genome-scale CRISPR/Cas9 gene-knockout screening is applied in discovering potential therapeutic antitumor targets in the cancer cells’ genomes and identified the important role of PTPN11 in pediatric rhabdoid tumors ( Oberlick et al, 2019 ). Genome-scale CRISPR/Cas9 gene-knockout screening can also be applied to study protein function and to explore new therapeutic targets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In recent years, CRISPR/Cas9 has been widely applied in altering genomes to activate or to repress the expression of genes; thus, its application accelerates the study of the mechanism of tumorigenesis and the development of cancer therapy ( Lee et al, 2019 ). A recent study demonstrated that genome-scale CRISPR/Cas9 gene-knockout screening is applied in discovering potential therapeutic antitumor targets in the cancer cells’ genomes and identified the important role of PTPN11 in pediatric rhabdoid tumors ( Oberlick et al, 2019 ). Genome-scale CRISPR/Cas9 gene-knockout screening can also be applied to study protein function and to explore new therapeutic targets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We next aimed to nominate potential targets for pharmacologic inhibition in ATRTs. To first test the coherence of genetic and chemical vulnerabilities in our dataset, we used the Drug Signatures Database (Yoo et al, 2015) to benchmark our screens based on the previously described sensitivity of ATRTs to tyrosine kinase inhibitors (Oberlick et al, 2019;Torchia et al, 2016). Using a set of non-ATRT cell lines previously screened with the Brunello library as a reference (DeWeirdt et al, 2020), we found 16 kinase inhibitor-induced signatures such as that produced by the multi-kinase inhibitor lenvatinib to be significantly enriched (nominal p value < 0.1) in ATRT-specific depleted genes ( Figure S2H).…”
Section: Crispr/cas9 Knockout Screens Reveal Genetic Dependencies Of mentioning
confidence: 99%
“…Genome-scale CRISPR-Cas9 gene-knockout screens alone or in combination with small drug screenings are becoming increasingly employed in the study of pediatric cancers (Aguirre et al, 2016;Oberlick et al, 2019).…”
Section: Crispr/cas9 Technology To Unravel Oncogenic Drivers In Pediatric Soft Tissue Sarcomasmentioning
confidence: 99%
“…Through this approach, Oberlick et al discovered a dependency of rhabdoid cells on different receptor tyrosine kinases (RTKs) among which PDGFRA and MET (Oberlick et al, 2019). They demonstrated that these kinases are up-regulated following SMARCB1 loss in cells lines and primary samples providing a proliferative advantage (Oberlick et al, 2019).…”
Section: Crispr/cas9 Technology To Unravel Oncogenic Drivers In Pediatric Soft Tissue Sarcomasmentioning
confidence: 99%
See 1 more Smart Citation